Determination of anatomical diagnostic signs of aboveground parts of raw material of Thymus eremita Klok. - Аkhmetalimova, А.М.; Ishmuratova, М.Yu.; Ivasenko, S.А.; Loseva, I.V.; Ludwiczuk, A. (Publ.KarSU, 2018)
Species of genus Thymus are widely used as perspective medical plants with anti-oxide, antimicrobial, antiviral, acaridae activity. Introduction of new species in State Pharmacopoeia is a very important research. In present article the anatomic research of some areal bodies of Thymus eremita is presented. Raw material is gathered at Karkaraly Mountains (Karaganda region) in phase flowering. During the research it has been established that the studied species of a thyme possesses xero-mesophytes and xerophytes type of a structure which is expressed in a small size of epidermis cells of a leaf, existence of numerous large essential oil glandular of a rounded or oval shape, stomata are characterized by anomocytes type, are located mainly on the lower party of a leaf. The diagnostic signs of raw materials of Thymus eremita are determined: for a stalk — a type of the fibro vascular system, character of an arrangement and the size of a phloem and xylem, existence of a cavity; for a leaf — a structure of the top and lower epidermis, essential oil glandular, a structure of a mesophyll.
Thymus еremita Klok. дəрілік шикізатының жерүсті ағзаларының анатомиялық диагностикалық белгілерін анықтау
Определение анатомических диагностических признаков надземных органов сырья Thymus eremite Klok.
Keywords: Thymus eremita; medical raw material; anatomy; diagnostic signs; essential oil glandular; stomata; epidermis; receptacle